Synthesis of Zn/Al-ZnO Composite Using Zn/Al-Layered Double Hydroxide for Oxidative Desulfurization of 4-Methyldibenzothiophene - Risfidian Mohadi; Nur Ahmad; Sahrul Wibiyan; Zaqiya Artha Zahara; Erni Salasia Fitri; Mardiyanto; Idha Royani; Aldes Lesbani (Science and Technology Indonesia, 2023)
Zn/Al-ZnO composites made from Zn/Al-Layered Double Hydroxide base material and ZnO as a precursor were successfully made in this study. Characterization analysis using SEM-EDS, XRD, and FTIR. The SEM analysis results show the Zn/Al-LDH has a smooth surface, overlapping, and is prone to aggregation, resulting in non-uniform particle size. However, it forms a uniform grain shape. Zn/Al-ZnO have rough surfaces with uniform particle shape and size, and the presence of pores on the particle surface. EDS analysis shows the Zn element which is more abundant in Zn/Al-ZnO. XRD analysis of Zn/Al-LDH showed the hydrotalcite. XRD analysis on ZnO showed the hexagonal wurtzite crystal structure. Zn/Al-ZnO composites at an angle of 2θ show the same peak of the base material and the precursor. FTIR analysis of the composite revealed the presence of O-H groups at wave numbers 3445 cm−1, 1633 cm−1, and 1504 cm−1, indicating the presence of nitrate. Additionally, vibrations at wave numbers 1382 cm−1 corresponded to antisymmetric (v3) stretching of nitrate, while wave numbers 418 cm−1 and 606 cm−1 indicated metal-oxygen stretching vibrations. Of all the factors used in the desulfurization of 4-methyldibenzothiophene, Zn/Al-ZnO composites had the highest %conversion rate of both the base material and the precursor. The %conversion values of Zn/Al-ZnO at the time of contact were 99.40%, catalyst dosage 99.38%, solvent 99.10%, and temperature 99.56%, respectively. The catalyst is heterogeneous and reusable for the desulfurization of 4-methyldibenzothiophene.